PENGARUH PERSON ORGANIZATION FIT (PO FIT), MOTIVASI DAN CAREER PLATEAU TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (Studi pada Satuan Polisi Pamong Praja Kabupaten Pati) - Subur Wahyudi, 12.5202.0105 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study has aimed to examine and to analyze the influence of person organization fit, motivation and career plateau for performance on mediation organizational commitment and employee job satisfaction Satuan Polisi Pamong Praja Kabupaten Pati. Data collection used survey method for 103 respodens. They were public servant on Satpol PP with census methode. The technique of data testing used statistical method, they covered validity test, reliability test, multiple regression analysis, t-test and mediation test. They were used to test and to prove hypotheses ofÂ study. The result of validity test pointed out KMO value was 0,945 for person organization fit variable, 0,890 for motivation variable, 0,937 for career plateau variable, 0,923 for job satisfaction variable, 0,939 for organizational commitment variable, and 0,953 performance of working variable. They were reliable in test, so alpha cronbach value was over 0,7. Based on resulting of their analysis, its examining pointed out person organization fit and motivation influenced positive and significant for job satisfaction, organizational commitment and performance. While career plateau influenced negative and significant to job satisfaction, organizational commitment and performance. The influence of person organization fit, motivation and career plateau for performance of working against were stronger directly than mediation job satisfaction or organizational commitment. Keywords: person organization fit, motivation,career plateau, job satisfaction, organizational commitment, andperformance